Analysis of Models and Implementation of Contract Farming on Income in Broiler Chicken Business, Ranomeeto District, South Konawe Regency - Gafaruddin, Abdul; Alwi, La Ode; Ido, Irfan; Sudarmo, Hadi (Universitas Halu Oleo, 2022)
Model Analysis and Implementation of Contract Farming on Income in Broiler Chicken Business provides benefits for farmers and entrepreneurs (partners). This research aims to; (1) know the contract farming model for broiler business in Ranomeeto District, South Konawe Regency, (2) know the implementation of contract farming for broiler business in Ranomeeto District, South Konawe Regency, and (know the relationship between the implementation of contract farming and the income of broiler farmers in Ranomeeto District, South Konawe Regency. This research uses quantitative and qualitative methods. Determination of the sample in this study using the census method of as many as 15 respondents. The results of this study indicate that: (1) the contract farming model in the Bi-Partite contract farming model, (2) the implementation of contract farming in Ranomeeto District based on the provision of production facilities obtained a very high level of implementation, then the implementation of extension activities and the suitability of harvest time was obtained at a very high level. moderate implementation, (3) the relationship between the implementation of contract farming with income in Ranometo District, based on the correlation coefficient value of 0.771, is at the level of a strong relationship.Keywords: Broiler chicken, contract farming model, implementation of contract farming